Determination of moxifloxacin hydrochloride in AVELOX pharmacological formulations using modified potentiometer sensors - Kumar, Sachin; K. Sindhu, Sushil; Kumar, Praveen; Sharma, Amit; Sagadevan, Suresh (Polimery, 2021)
Three different carbon paste (CP), silk-screen (SP) and poly (vinyl chloride) (PVC) modified electrodes were obtained to verify the reliability of AVELOX, the generic name of which is Moxifloxacin HCl (AV-MOXH). The sensing membranes were containing AVELOX ion associated complexes with sodium tetraphenylborate (NaTPB), phosphomolybdic acid (PMA), phosphotungstic acid (PTA), and ammonium reineckate (RN) as electroactive materials. All three electrodes gave fast, viable, and near-Nernstian linear responses over a relative wide concentration range that ranged from 1.010-6 to 1.010-2 mol / L AV-MOXH at 25° C with a monovalent cationic decrease. The sensors demonstrated a good discernment of AV-MOXH from numerous inorganic and organic compounds such as glucose, sucrose, Na+, Ca+, etc. Additionally, the isothermal coefficients along with selectivity coefficients were calculated. The modified Screen Printed Electrode sensor appeared to be highly sensitive for the determination of AV-MOXH. The electrode response was observed in pH range 2–6 for ISPE electrodes and IPVC electrodes and 3–7 for ICPE electrodes under various temperature conditions. The short response time, lifetime validity, recovery, and all the methods of validation such as limit of detection and limit of quantification were estimated. The potentiometric method turned out to be suitable for determining AV-MOXH in pharmacological formulations, and the findings obtained are comparable to the “HPLC official method” in terms of the agreement. As a result, the postulated potentiometric approach was verified in accordance with IUPAC guidelines.